Translation Studies – The State of the Art - Wilss, Wolfram (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractTranslation has spoken with growing impact and urgency to mankind for more than two millennia. Not only has it facilitated the understanding of sociocultural structures, economico-political systems, and technological/technical processes; it has also pushed forward our knowledge of the world (including our awareness of “otherness”) and widened our (inter-) linguistic and (inter-)cultural horizon.